2020
DOI: 10.1128/jvi.01169-20
|View full text |Cite
|
Sign up to set email alerts
|

The Measles Virus V Protein Binding Site to STAT2 Overlaps That of IRF9

Abstract: Measles virus (MeV) is a highly immunotropic and contagious pathogen that can even diminish preexisting antibodies, and remains a major cause of childhood morbidity and mortality worldwide despite the availability of effective vaccines. MeV is one of the most extensively studied viruses with respect to mechanisms of JAK-STAT antagonism. Of the three proteins translated from the MeV P gene, P and V are essential for inactivation of this pathway. However, the lack of data from direct analyses of the underlying i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Many viruses target STAT2 to antagonize IFN signaling. Thus, MeV V protein binds to STAT2 [ 177 , 178 ]. Yellow fever virus NS5 protein also binds STAT2 but this interaction requires STAT2 activation by IFN [ 179 ].…”
Section: Viral Evasion Strategies: Blockade Of Ifn Signalingmentioning
confidence: 99%
“…Many viruses target STAT2 to antagonize IFN signaling. Thus, MeV V protein binds to STAT2 [ 177 , 178 ]. Yellow fever virus NS5 protein also binds STAT2 but this interaction requires STAT2 activation by IFN [ 179 ].…”
Section: Viral Evasion Strategies: Blockade Of Ifn Signalingmentioning
confidence: 99%
“…Structure–function analysis has suggested that the Cys-rich C-terminal domain (CTD), particularly the zinc fingers ( Figure 3 and Figure 4 ), of the V protein is required to stabilize the interactions of the V protein with DDB1, whereas direct binding occurs with the other regions (also see Figure 6 ) [ 105 , 106 , 107 , 108 , 109 ]. This is also supported by phylogenetic evidence; specifically, the three jeilongviruses that express V proteins incapable of zinc finger formation ( Figure 4 and Figure 5 ) also fail to affect STAT1 or STAT2 [ 110 ].…”
Section: Stat2 Degradation By the Ubiquitin–proteasome System (Ups)mentioning
confidence: 99%
“…Ultimately, V protein was proved to inhibit lysine 63 (K63)-linked polyubiquitination of IRF7 mediated by TRAF6, consequently preventing TLR7/9-dependent IFN production (Kitagawa et al, 2013). Apart from V protein discussed above, the C protein of SeV can bind to IKKα and inhibit the phosphorylation of Andrejeva et al, 2004;Komatsu et al, 2007;Sakaguchi et al, 2011;Schaap-Nutt et al, 2011;Svitek et al, 2014;Audsley et al, 2016;Sanz Bernardo et al Garcin et al, 2002;Nishio et al, 2002;Takeuchi et al, 2003;Shaw et al, 2004;Nishio et al, 2005;Nanda and Baron, 2006;Caignard et al, 2007;Devaux et al, 2007Devaux et al, , 2013Svitek et al, 2014;Ma et al, 2015;Oda et al, 2015;Li P. et al, 2019;Keiffer et al, 2020;Nagano et al, 2020 STAT2 V (CDV, HPIV4, MeV, MuV, NiV, PIV5, and PPRV) Nishio et al, 2002Nishio et al, , 2005Rodriguez et al, 2004;Ramachandran et al, 2008;Svitek et al, 2014;Nagano et Takeuchi et al, 2003Hela Caignard et al, 2007HEK293T Ramachandran et al, 2008HEK293T and 2fTGH Nagano et al, 2020None Devaux et al, 2007 IRF7, leading to the inhibition of TLR7/9 signaling. However, compared to full size C protein (aa 1-204), Y1 (aa 24-204), and Y2 (aa 30-204) could bind to IKKα and exhibit less ability to suppress TLR7/9 signaling, indicating that N-terminal of C protein is not required for interaction with IKKα.…”
Section: Toll-like Receptors Signaling Pathwaymentioning
confidence: 99%
“…STAT2 is a primary target for MeV V protein (Takeuchi et al, 2003;Caignard et al, 2007;Ramachandran et al, 2008). However, Nagano et al (2020) provided controversial evidence recently. They found that the different regions of V protein mediated the interactions with STAT1 or STAT2, and these interactions are independent of each other.…”
Section: Measles Virusmentioning
confidence: 99%
See 1 more Smart Citation